Comparison of left ventricular function using isometric exercise Doppler echocardiography in competitive runners and weightlifters versus sedentary individuals - Fisman, E. Z.; Embon, P.; Pines, A.; Tenenbaum, A.; Drory, Y.; Shapira, I.; Motro, M. (The American Journal of Cardiology, 1997)
It is unclear whether cardiovascular responses to heavy isometric exercise are changed by intensive training. We evaluated the effects of this type of exercise on left ventricular (LV) function in athletes engaged in static and dynamic sport, compared with sedentary persons, and looked for peculiarities in static athletes' responses that might reflect adaptive mechanisms to their specific activity. The study population comprised 45 men (age 24 +/- 5 years): 29 dynamic and 16 static athletes (runners and weightlifters, respectively). The control group consisted of 20 age and gender-matched healthy sedentary persons. All performed 50% of maximal voluntary contraction on a whole-body isometric exercise device for 2 minutes. Echocardiographic calculations were determined at rest and exercise. Upon exercise, stroke volume, cardiac output, end-diastolic volume, and ejection fraction increased significantly in athletes, while end-systolic volume and systemic vascular resistance decreased. In sedentary persons, stroke volume and resistance remained unchanged, cardiac output and LV volumes increased, and ejection fraction decreased from 67 +/- 5% to 60 +/- 5% (p <0.01 compared with rest; p <0.0001 compared with athletes). Whereas peak flow velocity decreased from 103 +/- 10 to 81 +/- 6 cm/s in sedentary persons, it increased from 112 +/- 9 to 126 +/- 8 cm/s in the static group and from 120 +/-3 to 126 +/- 9 cm/s in the dynamic athletes (p <0.0001 compared with the sedentary group). Mean acceleration decreased in the sedentary group, remained unchanged among the dynamic athletes, and increased among the static athletes. We conclude that cardiovascular responses to heavy isometric exercise are modified by intensive training. Athletes, taken as a group, react differently and adapt better than sedentary individuals. Moreover, among them, those involved in static sport show an improved cardiovascular adaptation to this type of exercise.